Pancreatic cancer cell line in responsive hydrogel microcapsules for drug evaluation - Taiyu Song; Hui Zhang; Guangling Liu; Yudong Qiu; Huan Wang (View, 2024)
Abstract Drug therapies are the cornerstone of systemic treatment for pancreatic cancer patients. However, the relative outcome of drug evaluation is often hampered by the complex microenvironment of pancreatic cancer due to the lack of reasonable tumor models. Here, we proposed a novel platform that integrated pancreatic adenocarcinoma cells encapsulated into hydrogel microcapsules for three‐dimensional (3D) tumor cultivation and antitumor agent evaluation. These hydrogel microcapsules contain alginate/poly (N‐isopropyl acrylamide) (alginate/PNIPAM) shells and carboxymethyl cellulose cores, which are generated through the microfluidic electrospray technique. The microcapsules have the feature of rapid response to temperature, by which they can regulate the internal pressure environment. Besides, benefiting from good monodispersity, precise size control, and biocompatibility of these microcapsules, these wrapped tumor cells have the capacity for proliferating spontaneously and forming 3D tumor spheroids with good cell viability. We have demonstrated that pancreatic adenocarcinoma cells encapsulated in the composite microcapsules with different PNIPAM concentrations showed different drug sensitivity, which could be ascribed to the influence of external pressures environment. These results indicate that the tumor spheroids coated in these responsive microcapsules have great potential in the analysis of antitumor drug sensitivity.